ASH1L mutation caused seizures and intellectual disability in twin sisters. (September 2021) - Liu, Hailing; Liu, De-Tian; Lan, Song; Yang, Yan; Huang, Jingjing; Huang, Jinbo; Fang, Ling
Highlights: A de novo ASH1L truncating mutation was identified in a twin sister who presented mild ID and refractory epilepsies. Systematic analysis of ASH1L mutations suggest the correlations between genotype and phenotype. ID patients had a higher frequency of null mutations than ASD patients, suggesting missense mutations correlated with ASD. Abstract: ASH1L mutations have been identified with variable phenotypes, including intellectual disability, autism spectrum disorder (ASD), and multiple congenital anomalies (MCA). However, the mechanisms underlying this phenotypic variation remain unknown. Here, we present twin sisters exhibiting mild intellectual disability and seizures. Whole-exome sequencing of the family revealed a novel de novo heterozygous sequence variant, NM_018489.2: c.2678dup (p.Lys894*) in exon 3 of ASH1L which was estimated to be pathogenic. Furthermore, we reviewed previously reported ASH1L mutations in order to evaluate genotype-phenotype correlations for ASH1L variants. We found that patients with missense mutations in ASH1L appeared to present with more severe phenotypes and a higher likelihood of ASD than those with truncating mutations. The relationship between phenotype and genotype reported across several patients may help to explain the mechanisms underlying the phenotypic variation commonly observed between ASH1L mutations.